2015
DOI: 10.1186/s13195-014-0090-1
|View full text |Cite
|
Sign up to set email alerts
|

The monoaminergic footprint of depression and psychosis in dementia with Lewy bodies compared to Alzheimer’s disease

Abstract: IntroductionDepression and psychosis are two of the most severe neuropsychiatric symptoms (NPS) in dementia with Lewy bodies (DLB) and Alzheimer’s disease (AD). Both NPS have negative effects on cognitive performance and life expectancy. The current study aimed to investigate and compare monoaminergic etiologies between both neurodegenerative conditions, given the lack of an efficient pharmacological treatment until present.MethodsEleven behaviorally relevant brain regions of the left frozen hemisphere of 10 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 75 publications
0
43
1
Order By: Relevance
“…Sutphen and colleagues (Sutphen et al, 2015) similarly found in middle-aged, cognitively normal participants that YKL-40 (i.e., C3LP1) levels increased with age and APOE4 status, where longitudinal but not baseline associations were seen with amyloid positivity. Kester and colleagues (Kester et al, 2015) found that YKL-40 levels at baseline and longitudinally were higher in patients with MCI and AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sutphen and colleagues (Sutphen et al, 2015) similarly found in middle-aged, cognitively normal participants that YKL-40 (i.e., C3LP1) levels increased with age and APOE4 status, where longitudinal but not baseline associations were seen with amyloid positivity. Kester and colleagues (Kester et al, 2015) found that YKL-40 levels at baseline and longitudinally were higher in patients with MCI and AD.…”
Section: Discussionmentioning
confidence: 99%
“…As microglial activation is important for potentiating specific aspects of AD pathogenesis (Bales et al, 2000), related biomarkers have been investigated such as Chitinase 3-like Protein 1 (C3LP1). C3LP1, a derivative of chitin protein, is a marker of macrophage/microglial activation (Canto et al, 2015; Kester et al, 2015; Kzhyshkowska et al, 2007; Lautner et al, 2011; Lee et al, 2011; Sutphen et al, 2015). Serum and CSF C3LP1 levels are increased in preclinical and early AD (Canto et al, 2015; Craig-Schapiro et al, 2010), further suggesting its potential utility.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is substantial evidence that the mPFC is one of the key regions involved in the pathogenesis of major depressive disorder [75-77]. More specifically, MRI and neurochemical studies revealed that DLB patients with depression had significant reductions in the cortical volume and serotonin level, suggesting reduced activities in areas of self-referential and visual perception networks [78, 79]. It is noteworthy that unlike the NPI-depression, a different depression scale, the GDS-15, used in our study, showed no correlation with eLORETA-ICA results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in patients with AD the levels of DA and NA are decreased in cortex and hippocampus, while those of 5‐HT are decreased in hippocampus . Furthermore, characteristic clinical symptoms of AD including depressive disorders, psychosis and memory impairment are related to alterations in serotonergic, catecholaminergic and cholinergic neurotransmissions . Although we are not able to explain all the in‐vivo effects, it is clear that the present increased monoaminergic levels in hippocampus and prefrontal cortex of the rat are the net observed effects of ASS234.…”
Section: Discussionmentioning
confidence: 57%